GERMAN AS THE LANGUAGE OF SCIENCE: PROBLEMS AND PERSPECTIVES - Akhmedova Dilnoza Abdumannonovna (Scholar Express Journal, 2022)
During the analysis of the situation in the sphere of modern scientific discourse in the national languages, the importance of detailed descriptions of the real linguistic situation not only for the establishment of normative values, but also for the prediction of development trends becomes evident. The article attempts to describe and analyze some of the features of modern professional scientific communication that have a direct impact on the development of both the language of German science in general and the language of German linguistics in particular.
Keywords: globalization; professional communication; lingua franca; scientific discourse